Improving Word Problem Solving of Immediate, Generalized, and Combined Structured Problems via Schema-Based Instruction. Issue 2 (14th March 2020) - Peltier, Corey; Lingo, Mindy E.; Deardorff, Malarie E.; Autry, Faye; Manwell, Carli R.
ABSTRACT: Instruction geared toward priming the underlying problem structures was suggested as an evidence-based practice for students with a learning disability. Schema-based instruction is one intervention aligned with this principle. We extended prior work by (a) using a teacher as the implementer, (b) providing teacher flexibility in intervention implementation, and (c) examining student performance for generalized and combined problem structures. The participants included fourth-grade students ( n = 5) identified with a disability who received supplementary mathematics instruction in a resource room setting. The independent variable was schema-based instruction and the dependent variable was mathematical problem-solving performance. To evaluate if a functional relation existed, a multiple-probe design across participants was used. A functional relation was established; however, student performance did not reach socially significant levels. The aggregated Tau-U effect size was 81% [CI90 61, 100%] and the aggregated BC-SMD was 1.72 [CI95 1.00, 2.49]. Implications for research and practice will be discussed in regard to implementation fidelity and dosage of remedial instruction.